Hambatan dan Harapan Pelanggan pada Perjalanan Pembelian Matcha di Matcha Bar XYZ - Puteri, Arneta Fergiane; Sadeli, Agriani Hermita (Universitas Galuh, 2026)
Growing interest in matcha among young urban consumers in Indonesia has driven the rapid growth of matcha bars offering diverse service experiences. Responding to this trend, XYZ launched its matcha bar in April 2025. However, customer reviews of XYZ’s matcha products remain relatively limited compared to competitors, indicating potential issues in the customer experience that warrant further investigation. This study aims to identify pain points and customer expectations that shape experiences before, during, and after purchasing matcha at XYZ. A descriptive qualitative approach with an intrinsic case study design was employed. Data were collected through in-depth interviews with fifteen customers, one barista, and the general manager using the Sequential Incident Technique (SIT). The data were analyzed using Braun and Clarke’s thematic analysis supported by NVivo 15. Data trustworthiness was ensured through triangulation, member checking, peer debriefing, audit trails, and thick description. The findings reveal several key pain points, including product misperceptions, limited digital information, unclear service communication, inconsistencies in product preparation, issues with product and packaging quality, an inadequate store environment, and weak post-purchase retention efforts. Customers also expressed expectations for better digital information, clearer product explanations, improved consistency in preparation and packaging aesthetics, a more comfortable and well-defined store concept, and more attractive post-purchase incentives. These findings provide a basis for developing strategies to enhance the overall customer experience at XYZ’s matcha bar.